Adhesive sheet and optical laminate

The pressure-sensitive adhesive sheet with a tailored light-diffusing adhesive layer addresses thermal misalignment issues, ensuring high durability and effective bonding with film members in liquid crystal displays, reducing air bubbles and moiré.

JP7602858B2Active Publication Date: 2024-12-19LINTEC CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2018122242
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2018-06-27
Publication Date
2024-12-19
Estimated Expiration
2038-06-27

AI Technical Summary

Technical Problem

Existing adhesive layers in liquid crystal displays with light-diffusing particles face issues of misalignment due to thermal expansion and contraction differences, leading to air bubbles, peeling, and reduced durability, especially when adjacent to polarizing plates, and are challenging to laminate with thin, functional films.

Method used

A pressure-sensitive adhesive sheet with a light-diffusing adhesive layer having a storage modulus of 0.1 MPa to 1.0 MPa, a haze value of 20% to 80%, and an adhesive force of 3.0 N/25mm or more, using silicone resin particles and a specific composition to ensure high durability and excellent bonding properties.

Benefits of technology

The adhesive sheet provides high durability, reduces air bubbles and foreign matter during lamination, and suppresses moiré occurrence, ensuring effective bonding with various film members, including polarizing plates and brightness-enhancing films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602858000003
    Figure 0007602858000003
  • Figure 0007602858000004
    Figure 0007602858000004
  • Figure 0007602858000001
    Figure 0007602858000001
Patent Text Reader

Abstract

To provide an adhesive sheet achieving high durability and excellent bonding property when various film members are adherends, and an optical laminate obtained by using the adhesive sheet.SOLUTION: An adhesive sheet 1 has at least an adhesive layer 11, in which the adhesive layer 11 contains light-diffusing fine particles, the adhesive layer 11 has a storage modulus of 0.1 MPa or more and 1.0 MPa or less at 23°C, and when the adhesive layer 11 is measured in accordance with JIS K7374:2007, the total value of image clarity for optical combs having widths of 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm and 2.0 mm is 250% or more and 480% or less, and the adhesive layer 11 has a haze value of 20% or more and 80% or less. An adhesive force of the adhesive sheet 1 with respect to a polyethylene naphthalate film is 3.0 N / 25 mm or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive sheet and an optical laminate, and in particular to a pressure-sensitive adhesive sheet suitable for laminating film members such as polarizing plates and brightness enhancing films, and an optical laminate obtained by using the pressure-sensitive adhesive sheet. [Background technology]

[0002] In liquid crystal displays, a backlight is generally used, but there is a problem that the light source of the backlight causes uneven brightness. In order to solve this problem, a light diffusion plate having a light diffusion function or a light diffusion adhesive layer is provided at any position of the laminate constituting the liquid crystal display, for example, at a position adjacent to the polarizing plate. In recent years, there has been a demand for thin liquid crystal displays, and for this purpose, it is useful to provide a light diffusion adhesive layer.

[0003] The light-diffusing adhesive layer is usually obtained by adding fine particles to the adhesive layer to increase the haze value. For example, Patent Document 1 discloses a light-diffusing adhesive layer formed from an adhesive composition containing a copolymer including at least one alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C14, at least one selected from the group consisting of a copolymerizable monomer having a hydroxyl group as a monomer having a copolymerizable functional group, a vinyl monomer having a nitrogen atom, and a monomer having an aromatic group, a crosslinking agent, and silicon-based particles, and having a transmittance of 90% or more, a haze value of 40% or more, a refractive index of 1.47 or more, and an interface reflectance between the copolymer and the silicon-based particles of 0.01% or more. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-140380 A Summary of the Invention [Problem to be solved by the invention]

[0005] In general, when fine particles are added to an adhesive layer, there is concern about durability problems such as the occurrence of displacement at the interface between the fine particles and the adhesive due to thermal history caused by differences in thermal expansion or thermal shrinkage between the fine particles and the adhesive, which may result in the generation of air bubbles. In particular, when the light-diffusing adhesive layer is adjacent to a polarizing plate, the polarizing plate is prone to shrink due to thermal history, so that stress remains in the light-diffusing adhesive layer, and peeling is likely to occur at the interface due to the stress.

[0006] On the other hand, in order to impart durability to the light-diffusing pressure-sensitive adhesive layer, it is conceivable to increase the storage modulus by UV curing in addition to heat curing, but in that case, the adhesion to the film member is deteriorated, and there arises a problem that air bubbles or foreign matter are easily mixed in during lamination.

[0007] In addition, the protective film configurations of recent polarizing plates are diverse, and may require bonding with a brightness enhancing film. However, the difficulty of bonding recent polarizing plates and brightness enhancing films is increasing year by year due to the pursuit of functionality and thinness, and there is a problem that the light diffusing pressure-sensitive adhesive layer described in Patent Document 1 does not provide sufficient durability.

[0008] The present invention has been made in consideration of the above-mentioned circumstances, and aims to provide an adhesive sheet that exhibits high durability and excellent adhesion when various film members are used as adherends, and an optical laminate obtained using the adhesive sheet. [Means for solving the problem]

[0009] In order to achieve the above-mentioned object, firstly, the present invention provides an adhesive sheet having at least an adhesive layer, the adhesive layer containing light diffusing microparticles, the adhesive layer having a storage modulus at 23°C of 0.1 MPa or more and 1.0 MPa or less, the adhesive layer having a total image clarity of 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm and 2.0 mm optical combs measured in accordance with JIS K7374:2007 of 250% or more and 480% or less, the adhesive layer having a haze value of 20% or more and 80% or less, and the adhesive strength of the adhesive sheet to a polyethylene naphthalate film of 3.0 N / 25 mm or more (Invention 1).

[0010] The pressure-sensitive adhesive sheet according to the above invention (Invention 1) has excellent light diffusibility and exhibits high durability when adhered to various film members, such as polarizing plates having various protective films and brightness-enhancing films. Furthermore, the pressure-sensitive adhesive sheet is less likely to be contaminated with air bubbles or foreign matter during application, and is less likely to curl, so it has excellent adhesion to film members. Furthermore, the pressure-sensitive adhesive sheet can suppress the occurrence of moire in liquid crystal displays.

[0011] In the above invention (Invention 1), the thickness of the pressure-sensitive adhesive layer is preferably 5 μm or more and 20 μm or less (Invention 2).

[0012] In the above inventions (Inventions 1 and 2), it is preferable that the light diffusing fine particles are made of a silicone resin (Invention 3).

[0013] It is preferable that the adhesive sheet according to the above inventions (Inventions 1 to 3) comprises two release sheets, and the adhesive layer is sandwiched between the release sheets so as to be in contact with the release surfaces of the two release sheets (Invention 4).

[0014] The pressure-sensitive adhesive sheets according to the above inventions (Inventions 1 to 4) are preferably used to bond two film members together (Invention 5).

[0015] Secondly, the present invention provides an optical laminate comprising a first optical member, a second optical member, and a pressure-sensitive adhesive layer for bonding the first optical member and the second optical member to each other, wherein the pressure-sensitive adhesive layer is the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet (Inventions 1 to 5) (Invention 6).

[0016] In the above invention (Invention 6), at least one of the first optical member and the second optical member is preferably a film member (Invention 7). Effect of the Invention

[0017] The pressure-sensitive adhesive sheet according to the present invention exhibits high durability and excellent adhesion when various film members are used as adherends. In addition, the optical laminate according to the present invention has high durability and is less likely to contain air bubbles or foreign matter. [Brief description of the drawings]

[0018] [Figure 1] 1 is a cross-sectional view of a pressure-sensitive adhesive sheet according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a cross-sectional view of an optical laminate according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, an embodiment of the present invention will be described. [Adhesive sheet] The pressure-sensitive adhesive sheet according to one embodiment of the present invention has at least a pressure-sensitive adhesive layer, and the pressure-sensitive adhesive layer contains light-diffusing fine particles. The pressure-sensitive adhesive layer has a storage modulus of 0.1 MPa or more and 1.0 MPa or less at 23°C, and the pressure-sensitive adhesive layer has a total image clarity of 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm and 2.0 mm optical combs measured according to JIS K7374:2007 of 250% or more and 480% or less, the pressure-sensitive adhesive layer has a haze value of 20% or more and 80% or less, and the pressure-sensitive adhesive sheet (pressure-sensitive adhesive layer) has an adhesive strength to a polyethylene naphthalate film of 3.0 N / 25 mm or more. The polyethylene naphthalate film is not corona-treated.

[0020] According to the pressure-sensitive adhesive sheet satisfying the above composition and physical properties, when various film members, such as polarizing plates having various protective films and brightness-improving films, are used as adherends, the sheet exhibits high durability while having excellent light diffusion properties. For example, even when a laminate obtained by bonding a polarizing plate having a saponified triacetyl cellulose protective film and a non-alkali glass plate through the adhesive layer of the pressure-sensitive adhesive sheet, and a laminate obtained by bonding a polarizing plate having a non-saponified triacetyl cellulose protective film and a non-alkali glass plate are placed under durability conditions of 85°C, 85% RH, and 500 hours, the occurrence of lifting, peeling, foaming, streaks, etc. is suppressed. Such excellent durability is exhibited even when the thickness of the adhesive layer is relatively thin.

[0021] In addition, the adhesive sheet having the above physical properties is less likely to be contaminated with air bubbles or foreign matter during lamination, and is less likely to curl, so that the adhesive sheet has excellent lamination properties with film members. Furthermore, the adhesive sheet having the above physical properties can suppress the occurrence of moire in liquid crystal displays.

[0022] The storage modulus of the adhesive layer at 23°C is preferably relatively low from the viewpoint of preventing air bubbles from being mixed in during lamination and preventing curling, and is required to be 1.0 MPa or less, preferably 0.8 MPa or less, and particularly preferably 0.6 MPa or less. On the other hand, particularly from the viewpoint of durability, the storage modulus of the adhesive layer at 23°C is required to be 0.1 MPa or more, preferably 0.15 MPa or more, and particularly preferably 0.20 MPa or more. The storage modulus in this specification is a value measured by a torsional shear method at a measurement frequency of 1 Hz in accordance with JIS K7244-6. Specifically, it is as shown in the test example described later.

[0023] Furthermore, particularly from the viewpoint of suppressing the occurrence of moire, the image clarity (total value) is 480% or less, preferably 450% or less, and particularly preferably 430% or less, while from the viewpoint of display visibility, the image clarity (total value) must be 250% or more, preferably 300% or more, and particularly preferably 350% or more.

[0024] Here, the image clarity is measured by passing the amount of parallel light rays transmitted through a test specimen through an optical comb having a transmitting portion and a light-shielding portion. The smaller the width (comb width) between the transmitting portion and the light-shielding portion of the optical comb, the higher the image clarity. The image clarity is measured according to the transmission method of JIS K7374:2007.

[0025] In particular, from the viewpoint of suppressing the occurrence of moire, the haze value of the adhesive layer must be 20% or more, preferably 30% or more, particularly preferably 35% or more, and more preferably 40% or more. On the other hand, from the viewpoint of visibility of the liquid crystal display, the haze value of the adhesive layer is 80% or less, preferably 70% or less, and particularly preferably 60% or less. The haze value in this specification is a value measured in accordance with JIS K7136:2000.

[0026] Also, from the viewpoint of durability, the adhesive strength must be 3.0N / 25mm or more, preferably 3.3N / 25mm or more, and more preferably 3.5N / 25mm or more. The upper limit of the adhesive strength is not particularly limited, but is preferably 30N / 25mm or less, more preferably 20N / 25mm or less, and even more preferably 10N / 25mm or less. In addition, since polyethylene naphthalate film, especially polyethylene naphthalate film not subjected to corona treatment, is a material with very low adhesion, the adhesive strength to the polyethylene naphthalate film tends to be considerably lower than the adhesive strength to glass or polyethylene terephthalate film. Generally, the brightness improvement film uses polyethylene naphthalate film.

[0027] Here, the adhesive strength in this specification basically refers to the adhesive strength measured by the 180-degree peeling method in accordance with JIS Z0237:2009, and the measurement sample is 25 mm wide and 100 mm long, and the measurement sample is attached to the adherend and pressurized at 0.5 MPa and 50°C for 20 minutes, and then left to stand for 24 hours under conditions of normal pressure, 23°C and 50% RH, and then measured at a peeling speed of 300 mm / min.

[0028] The light diffusing fine particles contained in the pressure-sensitive adhesive layer may be any fine particles as long as the pressure-sensitive adhesive layer can satisfy the above-mentioned physical properties.

[0029] Examples of the light-diffusing fine particles include inorganic fine particles such as silica, calcium carbonate, aluminum hydroxide, magnesium hydroxide, clay, talc, and titanium dioxide; organic light-transmitting fine particles such as acrylic resin, polystyrene resin, polyethylene resin, and epoxy resin; and fine particles made of silicon-containing compounds having an intermediate structure between inorganic and organic such as silicone resin (for example, Tospearl series manufactured by Momentive Performance Materials Japan). Among them, fine particles made of silicone resin are preferable. This makes it easier for the adhesive sheet to satisfy the above-mentioned haze value and image clarity. The above light-diffusing fine particles may be used alone or in combination of two or more kinds.

[0030] The shape of the light diffusing fine particles is preferably spherical fine particles with uniform light diffusion. The average particle diameter of the light diffusing fine particles measured by the centrifugal sedimentation light transmission method is preferably 1.0 μm or more as a lower limit, particularly preferably 2.0 μm or more, and more preferably 3.0 μm or more. When the lower limit of the average particle diameter is as above, it becomes easy to develop haze and to reduce the image clarity to a predetermined degree. On the other hand, the upper limit of the average particle diameter is preferably 10 μm or less, particularly preferably 8 μm or less, and more preferably 6 μm or less. When the upper limit of the average particle diameter is as above, it is easy to prevent the haze value from becoming too high or the image clarity from decreasing too much, and a high-definition display image can be displayed well. In addition, even if the adhesive layer has a low film thickness, it is easy to obtain high adhesive strength.

[0031] The average particle size measured by the centrifugal sedimentation light transmission method was measured using a centrifugal automatic particle size distribution measuring device (Horiba, Ltd., CAPA-700) using a measurement sample prepared by thoroughly mixing 1.2 g of microparticles and 98.8 g of isopropyl alcohol.

[0032] The content of the light diffusing microparticles in the adhesive layer may be any amount that satisfies the above-mentioned physical properties. Specifically, the content of the light diffusing microparticles is preferably 2.0% by mass or more, particularly preferably 4.0% by mass or more, and more preferably 6.0% by mass or more. The content of the light diffusing microparticles is preferably 20% by mass or less, particularly preferably 15% by mass or less, and more preferably 10% by mass or less. When the content of the light diffusing microparticles is within the above range, the above-mentioned haze value, image clarity, and adhesive strength are easily satisfied.

[0033] FIG. 1 shows a specific configuration of one example of the pressure-sensitive adhesive sheet according to this embodiment. 1, the adhesive sheet 1 is composed of two release sheets 12a, 12b and an adhesive layer 11 sandwiched between the two release sheets 12a, 12b so as to be in contact with the release surfaces of the two release sheets 12a, 12b. In this specification, the release surface of the release sheet refers to the surface of the release sheet that has releasability, and includes both a surface that has been subjected to a release treatment and a surface that exhibits releasability even without being subjected to a release treatment.

[0034] 1. Each component 1-1. Adhesive layer The type of adhesive constituting the adhesive layer 11 of the adhesive sheet 1 according to this embodiment is not particularly limited, and may be, for example, any of an acrylic adhesive, a polyester adhesive, a polyurethane adhesive, a rubber adhesive, a silicone adhesive, etc. The adhesive may be any of an emulsion type, a solvent type, or a solventless type, and may be any of a crosslinked type or a non-crosslinked type. Among them, an acrylic adhesive is preferred because of its excellent adhesive properties and optical properties.

[0035] The adhesive (particularly, an acrylic adhesive) constituting the adhesive layer 11 of the adhesive sheet 1 according to this embodiment preferably contains a thermally crosslinked product, and more preferably contains an active energy ray cured product, and more preferably contains both a thermally crosslinked product and an active energy ray cured product (including the case where the same component constitutes both a thermally crosslinked product and an active energy ray cured product). In other words, the adhesive is preferably a product obtained by thermally crosslinking an adhesive composition, and more preferably a product obtained by curing an adhesive composition with active energy rays, and more preferably a product obtained by thermally crosslinking and curing an adhesive composition with active energy rays. By being thermally crosslinked and cured with active energy rays, the above-mentioned physical properties are easily satisfied, and particularly high durability is obtained.

[0036] The adhesive composition having thermal crosslinking and active energy ray curing properties may contain an active energy ray curable (meth)acrylic acid ester polymer (for example, a (meth)acrylic acid ester polymer having active energy ray curing properties introduced into the side chain), a crosslinking agent (thermal crosslinking agent), and light diffusing fine particles, or may contain an active energy ray non-curable (meth)acrylic acid ester polymer, an active energy ray curable component, a crosslinking agent (thermal crosslinking agent), and light diffusing fine particles. From the viewpoint of strengthening the cohesive force between the polymers and improving the adhesion at the interface between the light diffusing fine particles and the adhesive component, it is preferable to contain an active energy ray non-curable (meth)acrylic acid ester polymer, a crosslinking agent (thermal crosslinking agent), an active energy ray curable component, and light diffusing fine particles. Hereinafter, the adhesive composition in this case will be mainly described.

[0037] The adhesive constituting the adhesive layer 11 of the adhesive sheet 1 according to this embodiment is preferably obtained by thermally crosslinking and active energy ray curing an adhesive composition (hereinafter sometimes referred to as "adhesive composition P") containing an active energy ray non-curable (meth)acrylic acid ester polymer (A), a thermal crosslinking agent (B), an active energy ray curable component (C), and light diffusing microparticles (D). In this specification, (meth)acrylic acid means both acrylic acid and methacrylic acid. The same applies to other similar terms. In addition, the term "polymer" is also intended to include the concept of "copolymer".

[0038] (1) Components of the adhesive composition (1-1) (Meth)acrylic acid ester polymer (A) The (meth)acrylic acid ester polymer (A) preferably contains a reactive functional group-containing monomer having a reactive functional group in the molecule as a monomer constituting the polymer. By containing this reactive functional group-containing monomer, it reacts with the crosslinking agent (B) described later through the reactive functional group derived from the reactive functional group-containing monomer, thereby forming a crosslinked structure (three-dimensional network structure), and a pressure-sensitive adhesive having a predetermined cohesive strength is obtained.

[0039] Preferred examples of the reactive functional group-containing monomer include a monomer having a hydroxyl group in the molecule (hydroxyl group-containing monomer), a monomer having a carboxyl group in the molecule (carboxyl group-containing monomer), a monomer having an amino group in the molecule (amino group-containing monomer), etc. These reactive functional group-containing monomers may be used alone or in combination of two or more kinds.

[0040] Among the reactive functional group-containing monomers, hydroxyl group-containing monomers and carboxyl group-containing monomers are preferred, and it is particularly preferred to contain at least a carboxyl group-containing monomer that can effectively improve the adhesive strength to various adherends (film members), and further it is preferred to contain both a hydroxyl group-containing monomer and a carboxyl group-containing monomer.

[0041] Examples of hydroxyl group-containing monomers include (meth)acrylic acid hydroxyalkyl esters such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. Among them, from the viewpoint of reactivity with the crosslinking agent (B), 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferred. These may be used alone or in combination of two or more.

[0042] Examples of carboxyl group-containing monomers include ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, and citraconic acid. Among them, acrylic acid is preferred from the viewpoint of adhesive strength and reactivity with the crosslinking agent (B). These may be used alone or in combination of two or more.

[0043] The (meth)acrylic acid ester polymer (A) preferably contains reactive functional group-containing monomers (total amount) as monomer units constituting the polymer in a lower limit of 1% by mass or more, particularly preferably 2% by mass or more, and more preferably 3% by mass or more. In particular, it is preferable to contain carboxyl group-containing monomers in a lower limit of 0.1% by mass or more, particularly preferably 0.5% by mass or more, and more preferably 1% by mass or more. In addition, it is preferable to contain hydroxyl group-containing monomers in a lower limit of 0.1% by mass or more, particularly preferably 1% by mass or more, and more preferably 2% by mass or more. This effectively improves the adhesive strength to various adherends (film members).

[0044] In addition, the (meth)acrylic acid ester polymer (A) preferably contains reactive functional group-containing monomers (total amount) as monomer units constituting the polymer in an amount of 15% by mass or less as an upper limit, particularly preferably 12% by mass or less, and more preferably 10% by mass or less. In particular, it is preferable to contain carboxyl group-containing monomers in an amount of 8% by mass or less as an upper limit, particularly preferably 6% by mass or less, and more preferably 5% by mass or less. In addition, it is preferable to contain hydroxyl group-containing monomers in an amount of 8% by mass or less as an upper limit, particularly preferably 6% by mass or less, and more preferably 5% by mass or less. This makes it possible to sufficiently secure the content of monomers other than reactive functional group-containing monomers, and the adhesive properties of the obtained adhesive are more excellent.

[0045] The (meth)acrylic acid ester polymer (A) preferably contains a (meth)acrylic acid alkyl ester as a monomer unit constituting the polymer. This allows the polymer to exhibit good adhesion. The alkyl group may be linear or branched.

[0046] From the viewpoint of adhesion, the (meth)acrylic acid alkyl ester is preferably a (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 1 to 20. Examples of the (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 1 to 20 include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, and stearyl (meth)acrylate.

[0047] Among the above, from the viewpoint of efficiently imparting adhesive strength, (meth)acrylic acid alkyl esters having an alkyl group with 2 to 12 carbon atoms are more preferred, and acrylic acid alkyl esters having an alkyl group with 5 to 10 carbon atoms are particularly preferred. Specifically, preferred examples include n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and isooctyl (meth)acrylate, and more preferred examples include n-butyl (meth)acrylate. These may be used alone or in combination of two or more.

[0048] From the viewpoint of imparting adhesiveness, the (meth)acrylic acid ester polymer (A) preferably contains, as monomer units constituting the polymer, 60% by mass or more, particularly preferably 65% ​​by mass or more, and even more preferably 70% by mass or more of (meth)acrylic acid alkyl esters having an alkyl group with a carbon number of 1 to 20. From the viewpoint of ensuring the content of other monomers, the (meth)acrylic acid alkyl esters are preferably contained in an amount of 95% by mass or less, particularly preferably 90% by mass or less, and even more preferably 85% by mass or less.

[0049] In addition, the (meth)acrylic acid ester polymer (A) preferably contains a monomer having an alicyclic structure in the molecule (an alicyclic structure-containing monomer) as a monomer unit constituting the polymer. When the alicyclic structure-containing monomer is contained, the bulky functional group of the monomer increases the distance between the (meth)acrylic acid ester polymers (A), thereby increasing the flexibility of the resulting pressure-sensitive adhesive and further improving the adhesive strength to various adherends (film members).

[0050] The carbon ring of the alicyclic structure may be a saturated structure or may have an unsaturated bond. The alicyclic structure may be a monocyclic alicyclic structure or a polycyclic alicyclic structure such as a bicyclic or tricyclic structure. The number of carbon atoms in the alicyclic structure is preferably 5 to 20, more preferably 6 to 15, and even more preferably 7 to 12.

[0051] Preferred examples of the alicyclic structure include those containing a cyclohexyl skeleton, a dicyclopentadiene skeleton, an adamantane skeleton, an isobornyl skeleton, a cycloalkane skeleton (cycloheptane skeleton, cyclooctane skeleton, cyclononane skeleton, cyclodecane skeleton, cycloundecane skeleton, cyclododecane skeleton, etc.), a cycloalkene skeleton (cycloheptene skeleton, cyclooctene skeleton, etc.), a norbornene skeleton, a norbornadiene skeleton, a polycyclic skeleton (cubane skeleton, basketane skeleton, hausan skeleton, etc.), a spiro skeleton, etc. Among these, those containing an adamantane skeleton or an isobornyl skeleton are preferred from the viewpoint of further improving the adhesive strength to various adherends.

[0052] The alicyclic structure-containing monomer is preferably a (meth)acrylic acid ester monomer having the above skeleton, specifically, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, adamantyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, etc., among which, adamantyl (meth)acrylate and isobornyl (meth)acrylate are preferred. These may be used alone or in combination of two or more.

[0053] From the viewpoint of increasing the adhesive strength of the resulting pressure-sensitive adhesive to various adherends, the (meth)acrylic acid ester polymer (A) preferably contains 1% by mass or more of an alicyclic structure-containing monomer as a monomer unit constituting the polymer, more preferably 2.5% by mass or more, and even more preferably 5% by mass or more. From the viewpoint of ensuring the content of other monomers, the content of the alicyclic structure-containing monomer is preferably 25% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less.

[0054] In addition, the (meth)acrylic acid ester polymer (A) preferably contains a monomer having a nitrogen atom in the molecule (nitrogen atom-containing monomer) as a monomer unit constituting the polymer. By containing a nitrogen atom-containing monomer, the adhesive strength to various adherends (film members) can be further improved. Examples of the nitrogen atom-containing monomer include a monomer having an amino group, a monomer having an amide group, and a monomer having a nitrogen-containing heterocycle, and among them, a monomer having a nitrogen-containing heterocycle is preferable. In addition, from the viewpoint of increasing the degree of freedom of the portion derived from the nitrogen atom-containing monomer in the higher-order structure of the pressure-sensitive adhesive formed, it is preferable that the nitrogen atom-containing monomer does not contain a reactive unsaturated double bond group other than one polymerizable group used in polymerization to form the (meth)acrylic acid ester polymer (A).

[0055] Examples of monomers having a nitrogen-containing heterocycle include N-(meth)acryloylmorpholine, N-vinyl-2-pyrrolidone, N-(meth)acryloylpyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-(meth)acryloylaziridine, aziridinylethyl (meth)acrylate, 2-vinylpyridine, 4-vinylpyridine, 2-vinylpyrazine, 1-vinylimidazole, N-vinylcarbazole, and N-vinylphthalimide. Among these, N-(meth)acryloylmorpholine, which exhibits superior adhesive strength, is preferred, and N-acryloylmorpholine is particularly preferred.

[0056] In addition, as the nitrogen atom-containing monomer, for example, (meth)acrylamide, N-methyl(meth)acrylamide, N-methylol(meth)acrylamide, N-tert-butyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-ethyl(meth)acrylamide, N,N-dimethylaminopropyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-phenyl(meth)acrylamide, dimethylaminopropyl(meth)acrylamide, N-vinylcaprolactam, monomethylaminoethyl(meth)acrylate, monoethylaminoethyl(meth)acrylate, monomethylaminopropyl(meth)acrylate, monoethylaminopropyl(meth)acrylate, dimethylaminoethyl(meth)acrylate, and the like can also be used. The above nitrogen atom-containing monomers may be used alone or in combination of two or more.

[0057] From the viewpoint of increasing the adhesive strength of the resulting pressure-sensitive adhesive to various adherends, the (meth)acrylic acid ester polymer (A) preferably contains 0.5% by mass or more of a nitrogen atom-containing monomer as a monomer unit constituting the polymer, more preferably 1% by mass or more, and even more preferably 1.5% by mass or more. From the viewpoint of ensuring the content of other monomers, the content of the nitrogen atom-containing monomer is preferably 10% by mass or less, more preferably 8% by mass or less, and especially preferably 6% by mass or less.

[0058] The (meth)acrylic acid ester polymer (A) preferably contains at least one of a carboxyl group-containing monomer, an alicyclic structure-containing monomer, and a nitrogen atom-containing monomer as a monomer unit constituting the polymer, and particularly preferably contains all of them. This allows the polymer to exhibit excellent adhesion even to a film member (particularly a polyethylene naphthalate film) that has not been subjected to corona treatment, for example. When a film member is subjected to corona treatment, there is a problem that foreign matter is easily mixed in, but by not performing corona treatment, such a problem can be avoided. Therefore, an optical laminate and, in turn, a display can be manufactured using a high-quality film member.

[0059] The (meth)acrylic acid ester polymer (A) may be a solution polymer obtained by a solution polymerization method or a solventless polymer obtained by irradiation with active energy rays, but is preferably a solution polymer, which makes it easy to form a thin pressure-sensitive adhesive layer.

[0060] The polymerization mode of the (meth)acrylic acid ester polymer (A) may be a random copolymer or a block copolymer.

[0061] The weight average molecular weight of the (meth)acrylic acid ester polymer (A) is preferably 500,000 or more, particularly preferably 650,000 or more, and more preferably 800,000 or more. The weight average molecular weight of the (meth)acrylic acid ester polymer (A) is preferably 3,000,000 or less, more preferably 2,500,000 or less, particularly preferably 2,000,000 or less, and more preferably 1,150,000 or less. When the weight average molecular weight of the (meth)acrylic acid ester polymer (A) is within the above range, the storage modulus and adhesive strength described above are easily satisfied. The weight average molecular weight in this specification is a value measured by gel permeation chromatography (GPC) in terms of standard polystyrene.

[0062] In the pressure-sensitive adhesive composition P, the (meth)acrylic acid ester polymer (A) may be used alone or in combination of two or more kinds.

[0063] The content of the (meth)acrylic acid ester polymer (A) in the pressure-sensitive adhesive composition P according to this embodiment is preferably 80% by mass or more, more preferably 82% by mass or more, and even more preferably 85% by mass or more. The content of the (meth)acrylic acid ester polymer (A) is preferably 99% by mass or less, more preferably 97% by mass or less, and even more preferably 95% by mass or less. When the content of the (meth)acrylic acid ester polymer (A) is within the above range, the above-mentioned physical properties are easily satisfied.

[0064] (1-2) Crosslinking agent (B) The crosslinking agent (B) crosslinks the (meth)acrylic acid ester polymer (A) by heating the pressure-sensitive adhesive composition P, and can satisfactorily form a crosslinked structure having a three-dimensional network structure. This makes it easier to satisfy the above-mentioned physical properties.

[0065] The crosslinking agent (B) may be any that reacts with the reactive functional group possessed by the (meth)acrylic acid ester polymer (A), and examples thereof include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, amine-based crosslinking agents, melamine-based crosslinking agents, aziridine-based crosslinking agents, hydrazine-based crosslinking agents, aldehyde-based crosslinking agents, oxazoline-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, ammonium salt-based crosslinking agents, etc. The crosslinking agent (B) may be used alone or in combination of two or more.

[0066] Here, when the (meth)acrylic acid ester polymer (A) contains a hydroxyl group-containing monomer as a constituent monomer unit, it is preferable to use an isocyanate-based crosslinking agent having excellent reactivity with hydroxyl groups as the crosslinking agent (B). When the (meth)acrylic acid ester polymer (A) contains a carboxyl group-containing monomer as a constituent monomer unit, it is preferable to use an epoxy-based crosslinking agent having excellent reactivity with carboxyl groups as the crosslinking agent (B). Furthermore, when the (meth)acrylic acid ester polymer (A) contains a hydroxyl group-containing monomer and a carboxyl group-containing monomer as constituent monomer units, it is preferable to use both an isocyanate-based crosslinking agent and an epoxy-based crosslinking agent as the crosslinking agent (B).

[0067] The isocyanate-based crosslinking agent contains at least a polyisocyanate compound. Examples of the polyisocyanate compound include aromatic polyisocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, and xylylene diisocyanate, aliphatic polyisocyanates such as hexamethylene diisocyanate, alicyclic polyisocyanates such as isophorone diisocyanate and hydrogenated diphenylmethane diisocyanate, and their biuret and isocyanurate forms, as well as adducts which are reactants with low-molecular active hydrogen-containing compounds such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil. Among these, trimethylolpropane-modified aromatic polyisocyanates, particularly trimethylolpropane-modified tolylene diisocyanate and trimethylolpropane-modified xylylene diisocyanate, are preferred from the viewpoint of reactivity with hydroxyl groups.

[0068] Examples of epoxy crosslinking agents include 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidyl-m-xylylenediamine, ethylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane diglycidyl ether, diglycidylaniline, diglycidylamine, etc. Among these, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane is preferred from the viewpoint of reactivity with a carboxy group.

[0069] The content (total amount) of the crosslinking agent (B) in the adhesive composition P is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more, based on 100 parts by mass of the (meth)acrylic acid ester polymer (A). The content is preferably 1.0 part by mass or less, more preferably 0.8 parts by mass or less, and even more preferably 0.5 parts by mass or less. When the content of the crosslinking agent (B) is within the above range, the above-mentioned physical properties are more easily satisfied.

[0070] In particular, the content of the isocyanate-based crosslinking agent is preferably 0.009 parts by mass or more, more preferably 0.045 parts by mass or more, and even more preferably 0.09 parts by mass or more, based on 100 parts by mass of the (meth)acrylic acid ester polymer (A). The content is preferably 0.9 parts by mass or less, more preferably 0.72 parts by mass or less, and even more preferably 0.46 parts by mass or less.

[0071] The content of the epoxy crosslinking agent is preferably 0.001 parts by mass or more, more preferably 0.005 parts by mass or more, and even more preferably 0.01 parts by mass or more, based on 100 parts by mass of the (meth)acrylic acid ester polymer (A). The content is preferably 0.1 parts by mass or less, more preferably 0.08 parts by mass or less, and even more preferably 0.04 parts by mass or less.

[0072] (1-3) Active energy ray-curable component (C) When the adhesive composition P according to the present embodiment contains an active energy ray curable component (C), it is presumed that in the adhesive obtained by thermally crosslinking and curing the adhesive composition P with active energy rays, the active energy ray curable components (C) polymerize with each other, and the polymerized active energy ray curable components (C) are entangled with the crosslinked structure (three-dimensional network structure) of the (meth)acrylic acid ester polymer (A). An adhesive having such a high-order structure easily satisfies the above-mentioned storage modulus and exhibits very excellent durability.

[0073] The active energy ray curable component (C) is not particularly limited as long as it is a component that is cured by irradiation with active energy rays and can obtain the above-mentioned effects, and may be any of a monomer, an oligomer, or a polymer, or a mixture thereof. Among them, a polyfunctional acrylate monomer that can obtain a pressure-sensitive adhesive having excellent durability can be preferably mentioned.

[0074] Examples of polyfunctional acrylate monomers include bifunctional monomers such as 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, neopentyl glycol adipate di(meth)acrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate, dicyclopentanyl di(meth)acrylate, caprolactone-modified dicyclopentenyl di(meth)acrylate, ethylene oxide-modified phosphoric acid di(meth)acrylate, di(acryloxyethyl)isocyanurate, allylated cyclohexyl di(meth)acrylate, ethoxylated isocyanuric acid di(meth)acrylate, ethoxylated bisphenol A diacrylate, and 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene; trifunctional types such as diglycerolpropane tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, propionic acid modified dipentaerythritol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, ethoxylated isocyanuric acid tri(meth)acrylate, propylene oxide modified trimethylolpropane tri(meth)acrylate, tris(acryloxyethyl)isocyanurate, ε-caprolactone modified tris-(2-(meth)acryloxyethyl)isocyanurate; tetrafunctional types such as diglycerol tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate; pentafunctional types such as propionic acid modified dipentaerythritol penta(meth)acrylate; and hexafunctional types such as dipentaerythritol hexa(meth)acrylate, caprolactone modified dipentaerythritol hexa(meth)acrylate. These may be used alone or in combination of two or more. From the viewpoint of compatibility with the (meth)acrylic acid ester polymer (A), the polyfunctional acrylate monomer preferably has a molecular weight of less than 1000.

[0075] Among the above, from the viewpoint of further improving the durability of the obtained adhesive, polyfunctional acrylate monomers containing an isocyanurate structure in the molecule and polyfunctional acrylate monomers containing a pentaerythritol structure in the molecule are preferred. As the polyfunctional acrylate monomers containing an isocyanurate structure in the molecule, ethoxylated ones are preferred, and in particular, it is preferred to use at least one of ethoxylated isocyanuric acid di(meth)acrylate and ethoxylated isocyanuric acid tri(meth)acrylate, and further, it is preferred to use both ethoxylated isocyanuric acid di(meth)acrylate and ethoxylated isocyanuric acid tri(meth)acrylate. In addition, as the polyfunctional acrylate monomers containing a pentaerythritol structure in the molecule, pentaerythritol tri(meth)acrylate is particularly preferred.

[0076] The content of the active energy ray curable component (C) in the adhesive composition P is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, particularly preferably 2 parts by mass or more, and even more preferably 5 parts by mass or more, relative to 100 parts by mass of the (meth)acrylic acid ester polymer (A). The content is preferably 20 parts by mass or less, more preferably 17 parts by mass or less, particularly preferably 12 parts by mass or less, and even more preferably 8 parts by mass or less. By having the content of the active energy ray curable component (C) within the above range, the storage modulus described above is more easily satisfied, and the durability of the adhesive obtained can be made superior, and the adhesive can have excellent adhesion.

[0077] (1-4) Light-diffusing particles (D) The light diffusing fine particles (D) contained in the adhesive composition P are as described above. The content of the light diffusing fine particles (D) in the adhesive composition P may be any amount that satisfies the above-mentioned physical properties, and specifically, the content is preferably 2 parts by mass or more, more preferably 4 parts by mass or more, and particularly preferably 8 parts by mass or more, relative to 100 parts by mass of the (meth)acrylic acid ester polymer (A). The content is preferably 20 parts by mass or less, more preferably 16 parts by mass or less, and particularly preferably 12 parts by mass or less. When the content of the light diffusing fine particles is within the above range, the above-mentioned physical properties are easily satisfied.

[0078] (1-5) Photopolymerization initiator (E) When ultraviolet rays are used as the active energy rays for curing the adhesive composition P, it is preferable that the adhesive composition P further contains a photopolymerization initiator (E). By containing the photopolymerization initiator (E) in this way, the active energy ray curable component (C) can be polymerized efficiently, and the polymerization curing time and the irradiation dose of the active energy rays can be reduced.

[0079] Examples of such photopolymerization initiators (E) include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin-n-butyl ether, benzoin isobutyl ether, acetophenone, dimethylaminoacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-propan-1-one, 4-(2-hydroxyethoxy)phenyl-2-(hydroxy-2-propyl)ketone, benzof Examples of the benzoxanthone include phenone, p-phenylbenzophenone, 4,4'-diethylaminobenzophenone, dichlorobenzophenone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tertiary-butylanthraquinone, 2-aminoanthraquinone, 2-methylthioxanthone, 2-ethylthioxanthone, 2-chlorothioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, benzyl dimethyl ketal, acetophenone dimethyl ketal, p-dimethylaminobenzoic acid ester, oligo[2-hydroxy-2-methyl-1[4-(1-methylvinyl)phenyl]propanone], 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, etc. These may be used alone or in combination of two or more.

[0080] The content of the photopolymerization initiator (E) in the adhesive composition P is preferably 0.1 parts by mass or more as a lower limit, and more preferably 1 part by mass or more, relative to 100 parts by mass of the active energy ray-curable component (C), and is preferably 30 parts by mass or less as an upper limit, and more preferably 15 parts by mass or less.

[0081] (1-6) Silane coupling agent (F) The pressure-sensitive adhesive composition P preferably further contains a silane coupling agent (F), which improves adhesion to an adherend and provides greater durability.

[0082] The silane coupling agent (F) is preferably an organosilicon compound having at least one alkoxysilyl group in the molecule, which has good compatibility with the (meth)acrylic acid ester polymer (A) and has optical transparency.

[0083] Examples of such silane coupling agents (F) include polymerizable unsaturated group-containing silicon compounds such as vinyltrimethoxysilane, vinyltriethoxysilane, and methacryloxypropyltrimethoxysilane; epoxy structure-containing silicon compounds such as 3-glycidoxypropyltrimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; mercapto group-containing silicon compounds such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, and 3-mercaptopropyldimethoxymethylsilane. Examples of the silane derivatives include amino group-containing silicon compounds such as 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, and 3-isocyanatepropyltriethoxysilane, and condensates of at least one of these with alkyl group-containing silicon compounds such as methyltriethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, and ethyltrimethoxysilane. These may be used alone or in combination of two or more.

[0084] The content of the silane coupling agent (F) in the adhesive composition P is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more, based on 100 parts by mass of the (meth)acrylic acid ester polymer (A). The content is preferably 1 part by mass or less, more preferably 0.5 parts by mass or less, and even more preferably 0.3 parts by mass or less.

[0085] (1-7) Various additives If desired, various additives that are commonly used in acrylic adhesives, such as an ultraviolet absorber, an antistatic agent, a tackifier, an antioxidant, a light stabilizer, a softener, a filler, a refractive index adjuster, and an anti-rust agent, can be added to the adhesive composition P. Note that polymerization solvents and dilution solvents described below are not included in the additives that constitute the adhesive composition P.

[0086] (2) Manufacturing of adhesive composition The adhesive composition P can be produced by producing a (meth)acrylic acid ester polymer (A), mixing the obtained (meth)acrylic acid ester polymer (A) with a crosslinking agent (B), an active energy ray curable component (C), and light diffusing microparticles (D), and, if desired, adding a photopolymerization initiator (E), a silane coupling agent (F), and additives.

[0087] The (meth)acrylic acid ester polymer (A) can be produced by polymerizing a mixture of monomers constituting the polymer by a normal radical polymerization method. The polymerization of the (meth)acrylic acid ester polymer (A) is preferably carried out by a solution polymerization method using a polymerization initiator as desired. Examples of the polymerization solvent include ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, acetone, hexane, methyl ethyl ketone, etc., and two or more of them may be used in combination.

[0088] Examples of the polymerization initiator include azo compounds and organic peroxides, and two or more of them may be used in combination. Examples of the azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane 1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl 2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane].

[0089] Examples of organic peroxides include benzoyl peroxide, t-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl)peroxydicarbonate, t-butyl peroxyneodecanoate, t-butyl peroxypivalate, (3,5,5-trimethylhexanoyl)peroxide, dipropionyl peroxide, and diacetyl peroxide.

[0090] In the above polymerization step, the weight average molecular weight of the resulting polymer can be adjusted by adding a chain transfer agent such as 2-mercaptoethanol.

[0091] When the (meth)acrylic acid ester polymer (A) is obtained, the crosslinking agent (B), the active energy ray curable component (C), the light diffusing fine particles (D), and optionally the photopolymerization initiator (E), the silane coupling agent (F), the additives, and the dilution solvent are added to the solution of the (meth)acrylic acid ester polymer (A) and mixed thoroughly to obtain the adhesive composition P (coating solution) diluted with the solvent. In addition, when a solid is used for any of the above components, or when precipitation occurs when mixed with other components in an undiluted state, the component may be dissolved or diluted alone in a dilution solvent beforehand and then mixed with other components.

[0092] Examples of the dilution solvent include aliphatic hydrocarbons such as hexane, heptane, and cyclohexane; aromatic hydrocarbons such as toluene and xylene; halogenated hydrocarbons such as methylene chloride and ethylene chloride; alcohols such as methanol, ethanol, propanol, butanol, and 1-methoxy-2-propanol; ketones such as acetone, methyl ethyl ketone, 2-pentanone, isophorone, and cyclohexanone; esters such as ethyl acetate and butyl acetate; and cellosolve-based solvents such as ethyl cellosolve.

[0093] The concentration and viscosity of the coating solution thus prepared may be within a range that allows coating, and are not particularly limited, and may be appropriately selected according to the situation. For example, the adhesive composition P is diluted so that the concentration is 10 to 60 mass %. In addition, when obtaining the coating solution, the addition of a dilution solvent or the like is not a necessary condition, and if the adhesive composition P has a viscosity that allows coating, it is not necessary to add a dilution solvent. In this case, the adhesive composition P becomes a coating solution in which the polymerization solvent of the (meth)acrylic acid ester polymer (A) is itself used as the dilution solvent.

[0094] (3) Formation of adhesive layer The adhesive layer 11 is composed of an adhesive obtained by thermally crosslinking and active energy ray curing the adhesive composition P. Such an adhesive layer 11 can be preferably formed by applying the adhesive composition P to a desired object, drying it, and then curing the adhesive composition P by irradiating it with active energy rays.

[0095] The adhesive composition P may be dried by air drying, but is usually dried by heat treatment (preferably hot air drying). When heat treatment is performed, the heating temperature is preferably 50 to 150° C., and more preferably 70 to 120° C. The heating time is preferably 10 seconds to 10 minutes, and more preferably 50 seconds to 2 minutes.

[0096] Here, the active energy ray refers to an electromagnetic wave or a charged particle ray having an energy quantum, and specific examples thereof include ultraviolet rays, electron beams, etc. Among active energy rays, ultraviolet rays are particularly preferred because they are easy to handle.

[0097] The ultraviolet irradiation can be performed by a high pressure mercury lamp, a fusion H lamp, a xenon lamp, etc., and the amount of ultraviolet irradiation is 50 to 1000 mW / cm illuminance. 2 The light intensity is preferably about 50 to 10,000 mJ / cm. 2 is preferably 80 to 5000 mJ / cm 2 More preferably, it is 200 to 2000 mJ / cm 2On the other hand, the irradiation with the electron beam can be carried out by an electron beam accelerator or the like, and the irradiation dose of the electron beam is preferably about 10 to 1000 krad.

[0098] The (meth)acrylic acid ester polymer (A) is crosslinked by the crosslinking agent (B) to form a crosslinked structure (three-dimensional network structure) by drying (heat treatment) the adhesive composition P. It is presumed that the multiple active energy ray curable components (C) are polymerized with each other by irradiating the adhesive composition P with active energy rays, and the polymerized active energy ray curable components (C) are entangled with the crosslinked structure of the (meth)acrylic acid ester polymer (A).

[0099] (4) Thickness of the adhesive layer The thickness of the adhesive layer 11 (measured according to JIS K7130) is preferably 3 μm or more as a lower limit, particularly preferably 5 μm or more, and more preferably 8 μm or more. The thickness of the adhesive layer 11 is preferably 20 μm or less as an upper limit, more preferably 18 μm or less, particularly preferably 16 μm or less, and more preferably 14 μm or less. Since the thickness of the adhesive layer 11 is relatively thin as described above, the obtained optical laminate and, in turn, the display body can be made thin. Even if the thickness of the adhesive layer 11 is relatively thin as described above, the above-mentioned physical properties are easily satisfied by using the adhesive composition P. Furthermore, even if the thickness of the adhesive layer 11 is relatively thin as described above, high durability is exhibited and excellent adhesion is obtained even when various film members are used as adherends.

[0100] 1-2.Release sheet Release sheets 12a and 12b protect adhesive layer 11 until adhesive sheet 1 is used, and are peeled off when adhesive sheet 1 (adhesive layer 11) is to be used. In adhesive sheet 1 according to this embodiment, one or both of release sheets 12a and 12b are not necessarily required.

[0101] Examples of the release sheets 12a and 12b include polyethylene films, polypropylene films, polybutene films, polybutadiene films, polymethylpentene films, polyvinyl chloride films, vinyl chloride copolymer films, polyethylene terephthalate films, polyethylene naphthalate films, polybutylene terephthalate films, polyurethane films, ethylene vinyl acetate films, ionomer resin films, ethylene-(meth)acrylic acid copolymer films, ethylene-(meth)acrylic acid ester copolymer films, polystyrene films, polycarbonate films, polyimide films, and fluororesin films. Crosslinked films of these films are also used. Furthermore, laminated films of these films may be used.

[0102] The release surfaces of the release sheets 12a and 12b (particularly the surfaces in contact with the adhesive layer 11) are preferably subjected to a release treatment. Examples of release agents used in the release treatment include alkyd-based, silicone-based, fluorine-based, unsaturated polyester-based, polyolefin-based, and wax-based release agents. It is preferable that one of the release sheets 12a and 12b is a heavy release type release sheet having a large release strength, and the other is a light release type release sheet having a small release strength.

[0103] There is no particular limitation on the thickness of the release sheets 12a and 12b, but it is usually about 20 to 150 μm.

[0104] 2. Manufacturing of adhesive sheets In one example of manufacturing the adhesive sheet 1, a coating solution of the adhesive composition P is applied to the release surface of one release sheet 12a (or 12b), and a heat treatment is performed to thermally crosslink the adhesive composition P to form a coating layer, and then the release surface of the other release sheet 12b (or 12a) is superimposed on the coating layer to laminate them. Then, the coating layer is cured by irradiating the coating layer with active energy rays through the release sheet 12a (or 12b), thereby forming the adhesive layer 11.

[0105] In another example of manufacturing the adhesive sheet 1, a coating solution of the adhesive composition P is applied to the release surface of one of the release sheets 12a (or 12b), a heat treatment is performed to thermally crosslink the adhesive composition P, and a coating layer is formed.Then, while the coating layer is still exposed, active energy rays are irradiated to harden the coating layer, forming the adhesive layer 11, and then a release sheet 12b (or 12a) is laminated on the adhesive layer 11.

[0106] The coating solution of the pressure-sensitive adhesive composition P can be applied by, for example, bar coating, knife coating, roll coating, blade coating, die coating, gravure coating, or the like.

[0107] 3. Physical properties (1) Gel fraction The gel fraction of the adhesive constituting the adhesive layer 11 is preferably 50% or more, more preferably 60% or more, particularly preferably 70% or more, and even more preferably 80% or more. The gel fraction is preferably 95% or less, particularly preferably 93% or less, and even more preferably 91% or less. When the gel fraction of the adhesive is within the above range, the adhesive has a predetermined cohesive strength, and the above-mentioned storage modulus and adhesive strength are easily satisfied.

[0108] (2) Adhesive strength The adhesive strength of the adhesive sheet 1 (adhesive layer 11) according to this embodiment to soda lime glass is preferably 10N / 25mm or more as a lower limit, particularly preferably 14N / 25mm or more, and more preferably 17N / 25mm or more. The adhesive strength of the adhesive sheet 1 (adhesive layer 11) according to this embodiment to alkali-free glass is preferably 8N / 25mm or more as a lower limit, particularly preferably 9N / 25mm or more, and more preferably 10N / 25mm or more. The adhesive strength of the adhesive sheet 1 (adhesive layer 11) according to this embodiment to a saponified triacetyl cellulose (TAC) film is preferably 3N / 25mm or more as a lower limit, particularly preferably 4N / 25mm or more, and more preferably 5N / 25mm or more. When the lower limit of the adhesive strength of the adhesive sheet 1 is as above, higher durability is exhibited when various film members are used as adherends.

[0109] The upper limit of each of the above adhesive strengths is not particularly limited, but the upper limit of the adhesive strength to soda lime glass is preferably 30 N / 25 mm or less, more preferably 27 N / 25 mm or less, and even more preferably 25 N / 25 mm or less. The upper limit of the adhesive strength to non-alkali glass is preferably 25 N / 25 mm or less, more preferably 23 N / 25 mm or less, and even more preferably 20 N / 25 mm or less. The upper limit of the adhesive strength to a saponified triacetyl cellulose film is preferably 15 N / 25 mm or less, more preferably 12.5 N / 25 mm or less, and even more preferably 10 N / 25 mm or less.

[0110] [Optical laminate] By using the pressure-sensitive adhesive sheet 1 according to this embodiment, an optical laminate that can be applied to a display such as a liquid crystal display can be obtained. A specific configuration of the optical laminate according to one embodiment of the present invention is shown in FIG. 2. As shown in FIG. 2, the optical laminate 2 according to this embodiment is configured to include a first optical member 21, a second optical member 22, and a pressure-sensitive adhesive layer 11 located therebetween and bonding the first optical member 21 and the second optical member 22 to each other. This pressure-sensitive adhesive layer 11 is the pressure-sensitive adhesive layer 11 of the pressure-sensitive adhesive sheet 1 described above.

[0111] Examples of displays to which the optical laminate 2 can be applied include liquid crystal (LCD) displays, light emitting diode (LED) displays, organic electroluminescence (organic EL) displays, electronic paper, etc. The display may be a touch panel.

[0112] The first optical member 21 and the second optical member 22 are preferably flexible film members. This allows the adhesive sheet 1 according to the present embodiment to exhibit its effects effectively. However, one or both of the first optical member 21 and the second optical member 22 may be hard members.

[0113] Examples of the first optical member 21 and the second optical member 22 include a polarizing plate, a polarizer, a brightness enhancement film, a retardation plate (retardation film), a viewing angle compensation film, a contrast enhancement film, a liquid crystal polymer film, a diffusion film, a semi-transmissive reflective film, a transparent conductive film, and a shatterproof film.

[0114] Examples of the polarizing plate include a polarizing plate in which triacetyl cellulose (TAC) films are laminated as protective films on both sides of a polyvinyl alcohol (PVA) polarizer, a polarizing plate in which one of the TAC films is replaced with a cycloolefin polymer film (COP polarizing plate), and a polarizing plate in which a TAC film is laminated as a protective film on one side of a PVA polarizer. The TAC film may be saponified or may not be saponified. In the case of a polarizing plate in which a TAC film is laminated on one side of a PVA polarizer, the adhesive layer 11 may be directly attached to the PVA polarizer.

[0115] Here, the polarizing plate is required to be thinner year by year. However, in a thin polarizing plate, the protective film is also thin. Therefore, the force to suppress the thermal shrinkage of the stretch-oriented polarizer under durable conditions is insufficient. As a result, the thermal shrinkage of the polarizing plate tends to increase and the durability tends to deteriorate. However, if the adhesive layer 11 in this embodiment is used, even such a thin polarizing plate can exhibit sufficient durability.

[0116] Therefore, from the viewpoint of further exerting the effect of durability in this embodiment, the thickness of the polarizing plate is preferably 150 μm or less, more preferably 100 μm or less, and further preferably 80 μm or less. The lower limit of the thickness of the polarizing plate is not particularly limited, but is usually about 10 μm.

[0117] Examples of the hard members include glass plates, plastic plates, and those having various functional layers (transparent conductive films, metal layers, silica layers, hard coat layers, anti-glare layers, etc.) thereon, as well as display modules such as liquid crystal (LCD) modules, light emitting diode (LED) modules, and organic electroluminescence (OLED) modules, optical components as part of a display module, and laminates including a display module.

[0118] At least one of the first optical member 21 and the second optical member 22 is preferably either a polarizing plate or a brightness enhancing film. A particularly preferred combination of the first optical member 21 and the second optical member 22 is a polarizing plate and a brightness enhancing film. In addition, it is preferable that a saponified TAC film or an unsaponified TAC film is located on the surface of the polarizing plate facing the pressure-sensitive adhesive layer 11.

[0119] In the optical laminate 2, the pressure-sensitive adhesive layer 11 has excellent light diffusibility and exhibits high durability when the above-mentioned various film members are used as adherends. For example, even when a laminate obtained by bonding a polarizing plate having a saponified TAC film to a non-alkali glass plate via the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet and a laminate obtained by bonding a polarizing plate having an unsaponified TAC film to a non-alkali glass plate are placed under durability conditions of 85°C, 85% RH, and 500 hours, the occurrence of lifting, peeling, foaming, streaks, etc. is suppressed. Such an effect is exhibited even when the thickness of the pressure-sensitive adhesive layer 11 is relatively thin.

[0120] To manufacture the optical laminate 2, as an example, one release sheet 12a of the adhesive sheet 1 is peeled off, and the exposed adhesive layer 11 of the adhesive sheet 1 is bonded to one surface of the first optical member 21. Next, the other release sheet 12b is peeled off from the adhesive layer 11 of the adhesive sheet 1, and the exposed adhesive layer 11 of the adhesive sheet 1 is bonded to the second optical member 22 to obtain a laminate. As another example, the order of bonding the first optical member 21 and the second optical member 22 may be reversed.

[0121] The adhesive sheet 1 according to the present embodiment has excellent adhesion to film members, so that air bubbles and foreign matter are unlikely to be mixed in and curling is unlikely to occur when the adhesive sheet 1 is adhered to the first optical member 21 and when the adhesive layer 11 is adhered to the second optical member 22. This allows efficient production of a high-quality optical laminate 2, and thus a display.

[0122] The above-described embodiments are described for the purpose of facilitating understanding of the present invention, and are not described for the purpose of limiting the present invention. Therefore, each element disclosed in the above embodiment is intended to include all design modifications and equivalents that fall within the technical scope of the present invention.

[0123] For example, either one of the release sheets 12a, 12b in the pressure-sensitive adhesive sheet 1 may be omitted. EXAMPLES

[0124] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.

[0125] Example 1 1. Preparation of (meth)acrylic acid ester polymers 84.5 parts by mass of n-butyl acrylate, 7.5 parts by mass of isobornyl acrylate, 2.5 parts by mass of N-acryloylmorpholine, 3.0 parts by mass of 2-hydroxyethyl acrylate, and 2.5 parts by mass of acrylic acid were copolymerized by solution polymerization to prepare a (meth)acrylic acid ester polymer (A). The molecular weight of this (meth)acrylic acid ester polymer (A) was measured by the following method, and the weight average molecular weight (Mw) was 1.1 million.

[0126] 2. Preparation of adhesive composition 100 parts by mass (solid content equivalent; the same applies below) of the (meth)acrylic acid ester polymer (A) obtained in the above step 1, 0.3 parts by mass of trimethylolpropane-modified tolylene diisocyanate (manufactured by Nippon Polyurethane Co., Ltd., product name "Coronate L") as an isocyanate-based crosslinking agent (B), 0.03 parts by mass of an epoxy-based crosslinking agent (B) (manufactured by Soken Chemical & Engineering Co., Ltd., "Kokazai E-AX"), 7.5 parts by mass of a mixture of ethoxylated isocyanuric acid di(meth)acrylate and ethoxylated isocyanuric acid tri(meth)acrylate (manufactured by Toagosei Co., Ltd., product name "Aronix M-315") as an active energy ray-curable component (C), and photopolymerization reaction product (D) was prepared. 10.0 parts by mass of microparticles (manufactured by Momentive Performance Materials Japan, product name "Tospearl 145", average particle size: 4.5 μm) made of silicone resin (a silicon-containing compound having an intermediate structure between inorganic and organic) as diffusive microparticles (D), 0.75 parts by mass of a mixture of benzophenone and 1-hydroxycyclohexyl phenyl ketone in a mass ratio of 1:1 as a photopolymerization initiator (E), and 0.2 parts by mass of 3-glycidoxypropyltrimethoxysilane as a silane coupling agent (F) were mixed, thoroughly stirred, and diluted with methyl ethyl ketone to obtain a coating solution of adhesive composition P.

[0127] Here, the formulations (solid content equivalent) of the pressure-sensitive adhesive composition when the (meth)acrylic acid ester polymer (A) is taken as 100 parts by mass (solid content equivalent) are shown in Table 1. The details of the abbreviations and the like shown in Table 1 are as follows. [(Meth)acrylic acid ester polymer (A)] BA: n-butyl acrylate IBXA: Isobornyl acrylate ACMO: N-Acryloylmorpholine MA: Methyl acrylate HEA: 2-hydroxyethyl acrylate AA: Acrylic acid [Isocyanate-based crosslinking agent (B)] TDI: Trimethylolpropane modified tolylene diisocyanate (manufactured by Nippon Polyurethane Co., Ltd., product name "Coronate L") XDI: Trimethylolpropane modified xylylene diisocyanate (Mitsui Chemicals, product name "Takenate D110N") [Active energy ray-curable component (C)] C1: A mixture of ethoxylated isocyanuric acid di(meth)acrylate and ethoxylated isocyanuric acid tri(meth)acrylate (manufactured by Toa Gosei Co., Ltd., product name "Aronix M-315") C2: Pentaerythritol triacrylate (triester 37%) (manufactured by Shin-Nakamura Chemical Co., Ltd., product name "A-TMM-3L") [Light Diffusion Particles (D)] D1: Microparticles made of silicone resin (a silicon-containing compound with an intermediate structure between inorganic and organic) with an average particle size of 4.5 μm (manufactured by Momentive Performance Materials Japan, product name "Tospearl 145") D2: Microparticles made of silicone resin (a silicon-containing compound with an intermediate structure between inorganic and organic) with an average particle size of 3.0 μm (manufactured by Momentive Performance Materials Japan, product name "Tospearl 130") D3: Microparticles made of silicone resin (a silicon-containing compound with an intermediate structure between inorganic and organic) with an average particle size of 2.0 μm (manufactured by Momentive Performance Materials Japan, product name "Tospearl 120")

[0128] 3. Formation of adhesive layer The coating solution of the adhesive composition P obtained in the above step 2 was applied by a knife coater to the release-treated surface of a heavy release type release sheet (manufactured by Lintec Corporation, product name "SP-PET752150"), one side of which was a polyethylene terephthalate film released and treated with a silicone-based release agent, and then heated at 90°C for 1 minute to form a coating layer. The surface of the coating layer side of the heavy release type release sheet obtained with the coating layer was bonded to the release-treated surface of a light release type release sheet (manufactured by Lintec Corporation, product name "SP-PET381130"), one side of which was a polyethylene terephthalate film released and treated with a silicone-based release agent.

[0129] Next, the coating layer was irradiated with ultraviolet light through the light release type release sheet under the following conditions to harden the coating layer and form a 12 μm thick adhesive layer. This produced an adhesive sheet having a configuration of heavy release type release sheet / adhesive layer (thickness: 12 μm) / light release type release sheet. <Ultraviolet irradiation conditions> -High pressure mercury lamp used ·Illuminance 200mW / cm 2 ,Light intensity 200mJ / cm 2 The UV illuminance and light intensity meter used is the UVPF-36 manufactured by Eye Graphics.

[0130] The thickness of the pressure-sensitive adhesive layer is a value measured using a constant pressure thickness measuring device (manufactured by Techclock Corporation, product name "PG-02") in accordance with JIS K7130.

[0131] [Examples 2 to 9, Comparative Examples 1 to 5] Adhesive sheets were produced in the same manner as in Example 1, except that the composition and weight average molecular weight (Mw) of the (meth)acrylic acid ester polymer (A), the type and amount of the isocyanate-based crosslinking agent (B), the type and amount of the active energy ray-curable component (C), the type and amount of the light-diffusing microparticles (D), the amount of the photopolymerization initiator (E), and the thickness of the adhesive layer were changed as shown in Table 1.

[0132] The weight average molecular weight (Mw) mentioned above is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC) under the following conditions (GPC measurement). <Measurement conditions> Measuring device: Tosoh HLC-8320 GPC columns (passed in the following order): Tosoh Corporation TSK gel superH-H TSK gel superHM-H TSK gel superH2000 Measurement solvent: Tetrahydrofuran ·Measurement temperature: 40℃

[0133] [Test Example 1] (Measurement of storage modulus) The release sheets were peeled off from the pressure-sensitive adhesive sheets obtained in the Examples and Comparative Examples, and multiple pressure-sensitive adhesive layers were laminated to a thickness of 3 mm. A cylindrical body with a diameter of 8 mm (height of 3 mm) was punched out from the resulting laminate of pressure-sensitive adhesive layers, and this was used as a sample.

[0134] The storage modulus (MPa) of the above samples was measured under the following conditions by a torsional shear method using a viscoelasticity measuring device (manufactured by Physica, product name "MCR300") in accordance with JIS K7244-6. The results are shown in Table 2. Measurement frequency: 1Hz Measurement temperature: 23℃

[0135] [Test Example 2] (Measurement of gel fraction) The adhesive sheets obtained in the examples and comparative examples were cut to a size of 80 mm x 80 mm, the adhesive layer was wrapped in a polyester mesh (mesh size 200), and the mass was measured using a precision balance. The mass of the mesh alone was subtracted to calculate the mass of the adhesive alone. This mass was designated as M1.

[0136] Next, the adhesive wrapped in the polyester mesh was immersed in ethyl acetate at room temperature (23°C) for 24 hours. The adhesive was then removed and air-dried for 24 hours in an environment with a temperature of 23°C and a relative humidity of 50%, and then dried in an oven at 80°C for 12 hours. After drying, the mass was weighed using a precision balance, and the mass of the adhesive alone was calculated by subtracting the mass of the mesh alone. The mass at this time was designated M2. The gel fraction (%) was expressed as (M2 / M1) x 100. The results are shown in Table 2.

[0137] [Test Example 3] (Measurement of image clarity) For the pressure-sensitive adhesive sheets obtained in the examples and comparative examples, an image clarity tester (manufactured by Suga Test Instruments, product name "ICM-10P") was used to measure the image clarity of five types of optical combs (comb widths: 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm, and 2.0 mm) in accordance with the transmission method of JIS K7374:2007, and the total value was calculated as the image clarity (%). The results are shown in Table 2.

[0138] [Test Example 4] (Haze value measurement) The adhesive layer of the adhesive sheet obtained in the examples and comparative examples was attached to soda lime glass to prepare a measurement sample. After background measurement was performed on the soda lime glass, the haze value (%) of the measurement sample was measured using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., product name "NDH-2000") in accordance with JIS K7136:2000. The results are shown in Table 2.

[0139] [Test Example 5] (Measurement of adhesive strength) The light release type release sheet was peeled off from the adhesive sheet obtained in the Examples and Comparative Examples, and the exposed adhesive layer was attached to an easy-adhesion layer of a polyethylene terephthalate (PET) film (manufactured by Toyobo Co., Ltd., product name "PET A4300", thickness: 100 μm) having an easy-adhesion layer to obtain a release sheet / adhesive layer / PET film laminate. The obtained laminate was cut into a width of 25 mm and a length of 100 mm to prepare a sample.

[0140] The heavy release type release sheet was peeled off from the above sample under an environment of 23°C and 50% RH, and the exposed adhesive layer was attached to soda lime glass (manufactured by Nippon Sheet Glass Co., Ltd.), non-alkali glass (manufactured by Corning, product name "Eagle XG"), a polarizing plate having a saponified triacetyl cellulose (TAC) protective film (saponified TAC), and a polyethylene naphthalate (PEN) film (manufactured by 3M, product name "3M-APF V3", thickness 26 μm, no corona treatment), and then pressurized at 0.5 MPa and 50°C for 20 minutes in an autoclave manufactured by Kurihara Seisakusho Co., Ltd. After that, the sample was left for 24 hours under conditions of 23°C and 50% RH, and the adhesive strength (N / 25 mm) was measured using a tensile tester (manufactured by Orientec, product name "Tensilon") at a peel speed of 300 mm / min and a peel angle of 180 degrees. The conditions other than those described here were in accordance with JIS Z0237:2009, and the measurements were carried out under these conditions. The results are shown in Table 2.

[0141] [Test Example 6] (Durability evaluation) The light release sheet was peeled off from the pressure-sensitive adhesive sheet obtained in the Examples and Comparative Examples, and the exposed pressure-sensitive adhesive layer was attached to a saponified triacetyl cellulose (TAC) protective film of a polarizing plate (thickness: 50 μm) having the TAC protective film, and then cut to a size of 23.5 cm × 30.5 cm.

[0142] Next, the heavy release type release sheet was peeled off from the laminate, and the exposed adhesive layer was attached to alkali-free glass (manufactured by Corning Incorporated, product name "Eagle XG"), after which it was pressurized at 0.5 MPa and 50°C for 20 minutes in an autoclave manufactured by Kurihara Seisakusho, and this was used as the evaluation sample.

[0143] The above evaluation sample was subjected to durability conditions of 85°C, 85% RH, and 500 hours, and then the presence or absence of lifting, peeling, foaming, and streaks was confirmed using a 10x magnifying glass. The durability (saponified TAC) was then evaluated according to the following evaluation criteria. The results are shown in Table 2. ◯: No lifting, peeling, bubbling or streaks were observed. ×: Any of lifting, peeling, bubbling or streaks was observed.

[0144] In addition, the durability (unsaponified TAC) was evaluated in the same manner as above when the adherend was a polarizing plate (thickness 50 μm) having a non-saponified triacetyl cellulose (TAC) protective film instead of the polarizing plate having a saponified triacetyl cellulose (TAC) protective film. The results are shown in Table 2.

[0145] [Test Example 7] (Evaluation of air bubble inclusion) The adhesive sheets obtained in the examples and comparative examples were cut into B4 size. Next, in a clean environment, a tabletop laminator (manufactured by Fujipla, product name "MEISTER LPD3214") was used to peel off the light release type release sheet from the adhesive sheet, and the exposed adhesive layer was attached to the triacetyl cellulose protective film of a polarizing plate (B4 size) having a saponified triacetyl cellulose protective film. The state of air bubbles mixed into the interface between the adhesive layer and the polarizing plate after bonding was visually confirmed. The above test was performed on 10 samples for each example, and air bubbles were evaluated according to the following evaluation criteria. The results are shown in Table 2. ⊚: The number of bubbles was less than 5 in all 10 samples. ◯: The number of bubbles was less than 5 in 7 to 9 out of 10 samples. Δ: The number of bubbles was less than 5 in 2 to 6 samples out of 10 samples. ×: 9 to 10 out of 10 samples had 5 or more bubbles.

[0146] [Test Example 8] (Evaluation of moire generation) A liquid crystal mask having a grid pattern with light-transmitting areas was produced by forming a metal deposition layer on a glass plate and performing resist processing and etching processing. The liquid crystal mask had the grid pattern divided into areas with sizes of 20 to 180 ppi at 20 ppi (pixels per inch) intervals.

[0147] Next, the light release type release sheet was peeled off from the adhesive sheet obtained in the Examples and Comparative Examples, and the exposed adhesive layer was attached to a liquid crystal display with a resolution of 264 ppi (manufactured by Apple Inc., product name "i-Pad"). Next, the heavy release type release sheet was peeled off from the adhesive layer.

[0148] The liquid crystal mask was placed at a distance of 2 cm from the adhesive layer, and the liquid crystal display was visually observed through the liquid crystal mask to confirm the presence or absence of moire. The occurrence of moire was evaluated according to the following evaluation criteria. The results are shown in Table 2. .DELTA.: No moire occurred in any section of the liquid crystal mask. ○: Moire occurred in only some (less than half) of the sections of the liquid crystal mask. △: Moire occurred in more than half of the LCD mask sections. ×: Moire occurred in all sections of the liquid crystal mask.

[0149] [Table 1]

[0150] [Table 2]

[0151] As can be seen from Table 2, the pressure-sensitive adhesive sheets produced in the examples exhibited high durability, and also had excellent adhesion with little air bubble inclusion during lamination. In addition, the pressure-sensitive adhesive sheets produced in the examples were also able to suppress the occurrence of moire in liquid crystal displays. [Industrial Applicability]

[0152] The pressure-sensitive adhesive sheet according to the present invention is suitable for use in bonding various film-like optical components together, for example, bonding a polarizing plate to a brightness enhancement film. The optical laminate according to the present invention is also suitable for use as a component of a liquid crystal display. [Explanation of symbols]

[0153] 1...Adhesive sheet 11...Adhesive layer 12a, 12b...Release sheet 2...Optical laminate 21...First optical member 22...Second optical member

Claims

1. A pressure-sensitive adhesive sheet having at least a pressure-sensitive adhesive layer, The pressure-sensitive adhesive layer contains light-diffusing fine particles (excluding those having a refractive index of 1.50 or more), The light diffusing fine particles have an average particle size of 3.0 μm or more; The pressure-sensitive adhesive layer has a storage modulus at 23° C. of 0.1 MPa or more and 1.0 MPa or less, The pressure-sensitive adhesive layer has a total image clarity of 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm, and 2.0 mm optical combs measured in accordance with JIS K7374:2007 of 250% or more and 480% or less, The haze value of the pressure-sensitive adhesive layer is 20% or more and 80% or less, The adhesive strength of the pressure-sensitive adhesive sheet to a polyethylene naphthalate film is 3.0 N / 25 mm or more. A pressure-sensitive adhesive sheet characterized by:

2. 2. The pressure-sensitive adhesive sheet according to claim 1, wherein the pressure-sensitive adhesive layer has a thickness of 5 μm or more and 20 μm or less.

3. 3. The pressure-sensitive adhesive sheet according to claim 1, wherein the light-diffusing fine particles are made of a silicone resin.

4. It has two release sheets, The pressure-sensitive adhesive layer is sandwiched between the two release sheets so as to be in contact with the release surfaces of the release sheets. The pressure-sensitive adhesive sheet according to any one of claims 1 to 3.

5. 5. The pressure-sensitive adhesive sheet according to claim 1, which is used to bond two film members together.

6. A first optical member; A second optical member; a pressure-sensitive adhesive layer that bonds the first optical member and the second optical member to each other; An optical laminate comprising: The pressure-sensitive adhesive layer is a pressure-sensitive adhesive layer of a pressure-sensitive adhesive sheet according to any one of claims 1 to 5. An optical laminate characterized by:

7. 7. The optical laminate according to claim 6, wherein at least one of the first optical member and the second optical member is a film member.

Citation Information

Patent Citations

  • Light-diffusing adhesive layer and light-diffusing adhesive film

    JP2015140380A

  • Polarization film with double-sided adhesive layers, manufacturing method thereof and picture display unit

    JP2016136238A

  • Optical laminate and surface light source device

    JP2017013347A

  • Pressure-sensitive adhesive composition, pressure-sensitive adhesive and optical film

    WO2010024103A1

  • Adhesive composition, adhesive agent, and adhesive sheet

    WO2015145633A1